A alfabetização é nossa! Contribuições da educação dialógica à alfabetização e ao letramento do campo: um estudo bibliográfico - Oliveira, Cristiane Fontes de (Universidade Federal de São Carlos, 2021)
This paper presents a qualitative research in the field of Education, focusing on literacy skills in the modality of rural education, specifically that literacy, as a teaching and learning process, offered to students living in agrarian reform settlements and other peasant communities that practice family agriculture, seeking to verify the contributions of research based on dialogical learning to this theme. This is a bibliographical study, dedicated to the analysis of articles gathered from international scientific indexing databases, with the objective of verifying, analyzing, characterizing, and categorizing the contributions of theories and practices that have, as one of their theoretical foundations, the dialogical learning perspective, especially Paulo Freire's studies on literacy skills in rural education. The research work sought to verify how dialogical education can collaborate to the development of school practices in literacy skills that better correspond to the educational needs of peasant populations. The data were analyzed using the techniques of Content Analysis and Communicative Methodology, with the theoretical input of Paulo Freire and other authors with a communicative base, that is, who take the dialogical perspective as a strategy to overcome inequalities, through critical and problematizing thinking, which is done in the social praxis and constitutes action and reflection in interaction. The research has shown that there is a consensus in the studies of rural education with dialogic foundation about the need to adopt teaching and learning methodologies in literacy skills of rural populations, which take into consideration the rural territorial identity, demonstrating that not paying attention to the specificities can generate exclusion, collaborating to the historical marginalization experienced by rural people. The studies also present a set of didactic and pedagogical indications that point to a specific methodology to literacy skills in rural contexts, in order to value and promote historically subjugated rural identities. It also shows the occurrence of two important subfields of international studies, “Place-based Education” and “Rural Literacies”, which were not found in the national sample set. Thus, this research intended to present contributions to the practice of teaching literacy skills in the modality of rural education, which can promote instrumental learning and critical consciousness and, thus, collaborate to the social sustainability of rural people and their territories, promoting the ethical commitment to help rural communities to think about their demands, problems and, above all, their own social, economic, and cultural survival.
Literacy is ours! Contributions of dialogic education to rural literacy: a bibliographic study
Keywords: Alfabetização; Letramentos rurais; Educação do Campo; Aprendizagem dialógica; Paulo Freire; Educação baseada no lugar; Literacy; Rural Literacies; Rural Education; Dialogical Learning; Place-based Education; CIENCIAS HUMANAS::EDUCACAO